Psychological and Pedagogical Foundations for Developing the Process of Cultural Identification in Art Education - Muzropova Guljamol Mardonovna (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article examines the psychological and pedagogical foundations for developing the process of cultural identification in art education. Cultural identification refers to the awareness, understanding, and internalization of cultural values, traditions, and artistic expressions, enabling individuals to relate personally and socially to their cultural heritage. In the context of art education, fostering cultural identification supports aesthetic perception, creativity, and socio-cultural competence among students and teachers. The study highlights theoretical frameworks, psychological mechanisms, and pedagogical strategies that contribute to the development of cultural identification. By engaging with art, analyzing cultural symbols, and participating in creative activities, learners enhance their self-awareness, cultural literacy, and reflective thinking. The article emphasizes that integrating these foundations into art education promotes the formation of culturally aware, ethically responsible, and aesthetically sensitive individuals, capable of appreciating, preserving, and innovating within their cultural contexts.